Evaluation of the nephroprotective effect of dapagliflozin in renal ischaemia-reperfusion injury in male rats: Foxo1 modulation and pyroptosis - Abdul-Husseein, Hajir Karim; Adnan Alzubaidi, Fatima (Pharmakeftiki, 2025)
Renal ischaemia-reperfusion injury (RIRI) significantly contributes to acute kidney injury, leading to high morbidity and mortality rates. This study has investigated the nephroprotective effects of dapagliflozin, a sodium-glucose co-transporter 2 inhibitor, on RIRI in male Wistar rats. Twenty four rats were divided into four groups (n=6 each): a sham group (without an induction of RIRI), a control group (with an induction of RIRI), a vehicle group (receiving an intraperitoneal injection of 10% v/v dimethyl sulfoxide in isotonic saline solution, 1 h before ischaemia), and a dapagliflozin-treated group (receiving an intraperitoneal injection of dapagliflozin at 1 mg/kg, 1 h before ischaemia). Ischaemia was induced by clamping the renal pedicles for 30 min, followed by 2 h of reperfusion. Histopathological analysis revealed marked renal tissue injury in the control and vehicle groups, while dapagliflozin administration reduced these injuries, suggesting that less than 50% of the renal tubules were affected as a result. Kidney injury molecule-1, caspase-1, and caspase-11 levels were found to be significantly elevated in the control and vehicle groups, but decreased in the dapagliflozin group. The forkhead box O1 gene (Foxo1) expression was also found significantly reduced as a result of the treatment. These findings suggest that dapagliflozin mitigates renal injury through the suppression of Foxo1 expression and pyroptosis, thereby improving renal cell integrity. This study highlights dapagliflozin’s potential as a nephroprotective agent against acute renal failure, as it can enhance renal cell survival and mitigate injury pathways.